(3eSFdI Yf cfjSI MGQg RhjdIs
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hGdUdGI hGdSdGe Ydi CTQa GdeQSdjf eMeO hBdg hUMHg CLeYjf hHYO agPg eSFdI cfjSI MGQJ RhjdI GdJi hbYJ ai Ref bGVi GdYSGcQ GdefUhQg HeUQ s
(3BNQgG (B:s
(3dCfG CbQQfGge Ydi eGge Ydjg adh CNPfGgGe HfbVgG cGf ajg fbV dYgOge hPdc dGjLhR GfJgi hGddg CYde HGdUhGH hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH(B3s
(3HgG fXGe GdJYbjHIs
(3HBNQg cdeI ddEeGe GdSHci HNUhU gPg GdeSFdIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3GdeLGejYs